2018
DOI: 10.1002/anie.201804111
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Temporal Control and Enabling Chain‐End Modification in Photoregulated Cationic Polymerizations by Using Iridium‐Based Catalysts

Abstract: Gaining temporal control over chain growth is a key challenge in the enhancement of controlled living polymerizations. Though research on photocontrolled polymerizations is still in its infancy, it has already proven useful in the development of previously inaccessible materials. Photocontrol has now been extended to cationic polymerizations using 2,4,6-triarylpyrylium salts as photocatalysts. Despite the ability to stop polymerization for a short time, monomer conversion was observed over long dark periods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Hawker et al reported that Ir(ppy) 3 could be utilized in visible light-induced atom transfer radical polymerization of methacrylates [9], acrylates [10], and to fabricate a 3D polymer brush [11]. Besides, many other metallic materials [12,13,14,15,16,17,18,19] have been developed to achieve living/controlled polymerization under irradiation by visible light as well.…”
Section: Introductionmentioning
confidence: 99%
“…Hawker et al reported that Ir(ppy) 3 could be utilized in visible light-induced atom transfer radical polymerization of methacrylates [9], acrylates [10], and to fabricate a 3D polymer brush [11]. Besides, many other metallic materials [12,13,14,15,16,17,18,19] have been developed to achieve living/controlled polymerization under irradiation by visible light as well.…”
Section: Introductionmentioning
confidence: 99%
“…[62,63] As with radical photoRAFT, temporal control is readily achieved by switching ON/OFF light irradiation, which can be further enhanced by selection of a photocatalyst with greater stability (i.e., iridium complexes). [64] An interesting application to emerge from this technology has been the ability to combine orthogonal cationic and radical RAFT polymerizations. Combining these mechanistically distinct transformations enables the synthesis of unique block and star polymers consisting of cationically and radically polymerizable monomers, which cannot be accessed by a single polymerization in isolation.…”
Section: Cationic (Photo-)raftmentioning
confidence: 99%
“…[ 62,63 ] As with radical photoRAFT, temporal control is readily achieved by switching ON/OFF light irradiation, which can be further enhanced by selection of a photocatalyst with greater stability (i.e., iridium complexes). [ 64 ]…”
Section: Nontraditional Activation Of Tctsmentioning
confidence: 99%
“…More recently, Fors reported a visible light‐regulated cationic RAFT polymerization in which the cationic propagating species is generated upon oxidation of the dormant thioester bond by a photoredox catalyst such as a pyrylium salt or an iridium complex (Fig. ) . Furthermore, by simultaneously using both oxidizing and reducing photocatalysts (PCs) for the common dormant species (trithiocarbonate) in the copolymerization of vinyl ethers and acrylates, both cationic and radical RAFT polymerizations were active and generated copolymers; the monomer compositions and sequences of these copolymers can be tuned by the wavelength of the light .…”
Section: Cationic Polymerizationmentioning
confidence: 99%